Chipless RFID sensors - Karmakar, Nemai Chandra, 1963-; Amin, Emran Md; Saha, Jhantu Kumar (Wiley, 2016)
"Providing a classification of smart materials based on sensing physical parameters (i.e. humidity, temperature, pH, gas, strain, light, etc.)"--